2019
DOI: 10.1111/dmcn.14425
|View full text |Cite
|
Sign up to set email alerts
|

Prestatus and status dystonicus in children and adolescents

Abstract: Aim To critically analyse the management of status dystonicus and prestatus dystonicus in children and adolescents, in order to examine clinical features, acute management, and risk of relapse in a paediatric cohort. Method Clinical, demographic, and therapeutic features were analysed according to disease severity. Risk of subsequent relapse was estimated through Kaplan–Meier curves. Results Thirty‐four patients (eight females, 26 males) experiencing 63 episodes of acute dystonia exacerbations at a tertiary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 30 publications
1
20
0
Order By: Relevance
“…However, due to scarcity of literature, non‐English papers were also assessed. Finally, 33 papers met our inclusion criteria and were included in this review 15,17‐48 . The reasons to exclude the other 133 articles were the following: congress abstracts (n = 37), described no patients (n = 25), full text not available (n = 18), unilateral pallidotomy (n = 15), Parkinson's disease (n = 12), no (motor) outcomes (n = 9), patients described before (n = 7), thalamotomy or other lesions (n = 6), no dystonia patients (n = 2), and DBS only (n = 2) ( FIGURE S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, due to scarcity of literature, non‐English papers were also assessed. Finally, 33 papers met our inclusion criteria and were included in this review 15,17‐48 . The reasons to exclude the other 133 articles were the following: congress abstracts (n = 37), described no patients (n = 25), full text not available (n = 18), unilateral pallidotomy (n = 15), Parkinson's disease (n = 12), no (motor) outcomes (n = 9), patients described before (n = 7), thalamotomy or other lesions (n = 6), no dystonia patients (n = 2), and DBS only (n = 2) ( FIGURE S1).…”
Section: Resultsmentioning
confidence: 99%
“…In 19 of 100 patients, a relapse of dystonic symptoms was reported (Table 1). One study reported relapsing SD 45 . Six patients were treated with DBS after bilateral pallidotomy, because their dystonic symptoms reappeared after temporary benefit 24,38,49 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reported mortality of status dystonicus has remained concerningly high at 10%, with current guidelines for management entirely based on expert opinion. Garone et al report the management and clinical course of 34 children experiencing 64 episodes of acute dystonia that required hospital admission. This report is welcome, not only for contributing to the sparse literature on status dystonicus, but also for the explicit demonstration that not all presentations with worsening dystonia are at the point at which they are actively life threatening.…”
mentioning
confidence: 99%